Effective English Teacher Professional Development from a Professional Perspective: Saudi Arabia Context - Elnadeef, Elsadig Ali Elsadig; Abdala, Ayman Hamad Elneil Hamdan (International Journal of Linguistics, Literature and Translation, 2022)
This study investigates the concept of effective teacher professional development based on professionalism perspective. It aims at explaining the concept of professionalism, focusing on the significance of professionalism in maintaining the quality of English teacher development, teaching English, and instructional processes. It demonstrates the fundamental requirements for an effective English teacher and effective teaching. The study is based on the hypothesis which proposes that teacher professional development leads to grand achievement in education. The study pinpoints that to be an English teacher; one must gain particular pedagogical, psycho-socio, and linguistics training; in addition, an English teacher is responsible for his/her ongoing professional development, which leads to teacher’s confidentiality and highly students’ achievement.